HATCHING AND GROWTH OF TRIPLOID AND TETRAPLOID OF (Heterobranchus longifilis) AND (Hetrobranchus bidorsalis) SUBJECTED TO ERYTHROCYTES MEASUREMENT - Hassan, Kabir Y.; Galambi, Abubakar Y.; Bashir, Labaran H.; Abubakar, Garba A.; Ismail, Mohammed; Bununu, Mohammad S.; Philip, Oateju O.; Yahaya, Abdullahi M.; Mashi, Farida, I.; Nuhu, Kabiru A.; Sani, Bala M. (FUDMA Journal of Sciences, 2026)
The study experimented (to exposed the hatching and growth) of triploid and tetraploid of heterobranchus longifilis and heterobranchus bidorsalis subjected to erythrocyte (measured),The purposed was to produce better stock of heterobranchus species in terms of growth performance through erythrocyte measurement,also to determine diploid, triploid,and tetraploid red blood cells for aquaculture benefits.This application is one of the major areas of biotechnology whose application to fish breeding lead to increase fish yield. triploid induction is a process whereby an entire chromosome set is added to a fertilized egg. Normal individuals are diploid (2N), receiving one chromosome set (1N) from each parent. Triploid (3N) individuals have an additional chromosome set derived from the second polar body (1N). The second polar body is produced during an egg’s meiotic cell division and is normally lost soon after fertilization. If appropriate shock is applied soon after fertilization, the second polar body is retained by the fertilized egg, thus producing a triploid individual. The fish was separated into three tanks of 500 litres water holding capacity of 1m x 1m3 representing the treatments. The data on red blood cells analysis and erythrocyte measurement were analysed using duncam multiple wide range test.This study shows that triploidy and tetraploidy could be induced in (H.longifilis and H.bidorsalis) by cold shock treatment, 3 minutes after fertilization at 50C for 20 minutes while tetraploidy could be induced by administering cold shock treatment, 30 minutes after fertilization at 50C for 10 minutes.